Val[a]idating the efficacy of commercial foaming cleaner and sanitizer for controlling Listeria innocua (surrogate for Listeria monocytogenes) in drains and potential translocation from the drain to the food contact surfaces - Saini, Jasdeep Kaur (Kansas State University, 2008)
Listeria monocytogenes is known to be an environmental contaminant in food processing facilities. Floor drains in processing environments harbor Listeria spp. due to continuous presence of humidity and organic substrates. The cleaning and washing activities undertaken may translocate the bacterial cells from the drain to the surrounding environment, thus contaminating food products being produced. This study validates the effectiveness of Johnson Diversey ‘Eliminex’ Foaming Drain Cleaner and Johnson Diversey ‘Final Step’ 512 sanitizer for inhibition of Listeria monocytogenes in drain surfaces and evaluates the potential for translocation of L. monocytogenes from drains to food contact surfaces in the surrounding environment using Listeria innocua as a surrogate. A 7x 7 x 8 feet flexi glass chamber was built in which a 10 inch diameter drain mounted on an aluminum cabinet was placed. The drain was inoculated with the surrogate organism, L. innocua, at specific time intervals and then treated with the given chemicals. Sponge samples were taken and bacterial populations were recovered on Tryptic Soy Agar (TSA), Modified Oxford Medium (MOX) and Thin Agar Layer MOX (TALMOX). Stainless steel coupons (6.4 x 1.9 x 0.1 cm) were hung at 3 different heights 1, 3 and 5 feet inside the chamber and cell translocation from the drain on to the stainless steel coupons was studied. Reductions up to 4 Log CFU/area or ml were seen at the drain surface, drain crate, drain pipe and wash water for both free cells and cells entrapped in biofilms Treatment had a significant effect (p<0.05) on the reduction of bacterial cells. The wash water showed the greatest reduction from 8 Log CFU/ml to est. 0.23 Log CFU/ml. The given cleaner and sanitizer were found to be effective for reducing Listeria spp. on drain surfaces. Results for the second part indicated translocation at all three heights with percentage translocation ranging between 2-17%. Significantly higher translocation (p<0.05) was seen at 1 foot, followed by 3 feet and 5 feet indicating the closer the height to the drain, the greater the number of bacterial cells that are able to transfer from the drain to the surrounding environment.
Validating the efficacy of commercial foaming cleaner and sanitizer for controlling Listeria innocua (surrogate for Listeria monocytogenes) in drains and potential translocation from the drain to the food contact surfaces
Keywords: Listeria monocytogenes; Listeria innocua; Drains; Food contact surfaces; Agriculture, Food Science and Technology (0359)